Developing The Creativity of Pencak Silat: A Systematic Literature Review - Deny Pradana Saputro; Nasuka Nasuka; M.E. Winarno; Sulaiman Sulaiman (Universitas Negeri Semarang, 2023)
Creativity is a very important element for students of pencak silat to have. This is because creativity contributes to helping a person achieve his desires. Given the importance of creativity which is needed in almost all aspects, this needs to be achieved through self-development. Based on this, this study aims to find out how to develop creativity in pencak silat. The method used in this study is a systematic literature review. Search range for articles in 2018-2023. The keywords used are